Reconfiguração de redes com recursos energéticos distribuídos no horizonte da ENEL distribuição São Paulo - (:unkn) unknown (Universidade Federal do Pampa, 2019)
As the generation capacity of DG is growing rapidly in recent years, distributed generation (DG) has a great influence on various aspects of power distribution networks. One aspect is the reconfiguration of the distribution system, which proposes to change the topology through sectioning devices, enabling actions that allow the operation of the system in a more adequate way. The flow of the distribution system goes only in one direction as it is operated in radial configuration and has larger line losses and the terminal voltage generally falls more compared to the transmission network. System reconfiguration can weaken the impact of this some way. The distribution network flow changes due to the influence of GD, the original network structure is generally no longer optimal for minimum power loss. It is in this scenario that this work aims to present a methodology based on the heuristic method called Branch Exchange, where it has as purpose to find new reconfigurations that meet the multi-objective functions and also to analyze the time demand profile of the system and to analyze the produced energy profile by distributed generation plants of different technologies. In order to prioritize criteria and select the best switching sequence, the multi-criteria AHP (Analytic Hierarchy Process) technique is used. The methodology is simulated in a real network of the distributor Enel Distribuição São Paulo, considering different scenarios of load and generation availability of distributed generators . Through the application of the method there were four topologies where there were reduction of the indicators of the objective function and one of them was chosen as a new optimal solution of the system.
Keywords: Engenharia elétrica; Geração distribuída; Redes de distribuição de energia elétrica; Recursos energéticos; Branch Exchange; Electrical engineering; Distributed generation; Electricity distribution networks; Energy resources; CNPQ::ENGENHARIAS